Survival Strategies of Urban Home-Based Culinary MSMEs in Surabaya Amid Digitalization without High-Tech Capital - Esti Retnaningtyas; Arief Budiman; Muis Murtadho (Indonesian Journal of Advanced Research, 2026)
This study examines survival strategies of home-based culinary MSMEs in Surabaya confronting digitalization without advanced technology. Using a qualitative phenomenological design grounded in the Resource-Based View (RBV), it investigates social capital, tacit knowledge, operational flexibility, and word-of-mouth marketing. Data from five MSME owners were collected through interviews, observation, and documentation, then thematically analyzed using NVivo 15. Findings indicate business resilience is fostered through localized networks, intergenerational culinary knowledge, adaptive operations, and interpersonal trust. The study concludes that non-digital MSMEs maintain competitiveness through VRIN-compliant internal resources, introducing the concept of "Resilience through Constraints" and challenging technology-centric assumptions about digital transformation.